2010
DOI: 10.1109/tmi.2009.2029097
|View full text |Cite
|
Sign up to set email alerts
|

Co-registration of White Matter Tractographies by Adaptive-Mean-Shift and Gaussian Mixture Modeling

Abstract: Abstract-In this paper we present a robust approach to the registration of white matter tractographies extracted from DT-MRI scans. The fibers are projected into a high dimensional feature space based on the sequence of their 3D coordinates. Adaptive mean-shift (AMS) clustering is applied to extract a compact set of representative fiber-modes (FM). Each FM is assigned to a multivariate Gaussian distribution according to its population thereby leading to a Gaussian Mixture model (GMM) representation for the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Recently, Durrleman et al (2014) improved and extended this framework on currents by using varifolds. Zvitia et al (2008Zvitia et al ( , 2010 used adaptive mean shift clustering to extract a number of representative fiber-modes. Each fiber mode was assigned to a multivariate Gaussian distribution according to its population thereby leading to a Gaussian mixture model (GMM) representation for the entire set of fascicles.…”
Section: Streamline-basedmentioning
confidence: 99%
“…Recently, Durrleman et al (2014) improved and extended this framework on currents by using varifolds. Zvitia et al (2008Zvitia et al ( , 2010 used adaptive mean shift clustering to extract a number of representative fiber-modes. Each fiber mode was assigned to a multivariate Gaussian distribution according to its population thereby leading to a Gaussian mixture model (GMM) representation for the entire set of fascicles.…”
Section: Streamline-basedmentioning
confidence: 99%
“…The choice of k is supported by previous research [10] which concluded this number to be good compromise between the complexity and fidelity to the original representation. The details of the different approaches to fiber reduction are given next.…”
Section: Methodsmentioning
confidence: 99%
“…So far, methods that have performed registration using unlabeled fiber tracts from the whole brain, e.g. [9, 21, 12], have been limited to subject-to-subject (pairwise) registration.…”
Section: Introductionmentioning
confidence: 99%